2016
DOI: 10.32929/2446-8355.2016v25n1p17-24
|View full text |Cite
|
Sign up to set email alerts
|

Remoção De Estruturas Vegetativas Nos Estádios Iniciais Sobre Características Produtivas E Morfofisiológicas Da Soja

Abstract: O objetivo deste estudo foi avaliar o desempenho produtivo e as características da soja após a remoção de estruturas vegetativas no desenvolvimento inicial. O trabalho foi conduzido na Fazenda Escola da UEL, nas safras 2012/13 e 2013/14, utilizando a cultivar BRS 360 RR, num delineamento em blocos casualizados com quatro tratamentos e cinco repetições. Os tratamentos foram: 1- Testemunha; 2- Remoção dos cotilédones em VC; 3- Corte do caule acima do nó cotiledonar em V1; 4- Corte do caule acima do nó das folhas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These authors observed in two treatments, that plants submitted to cuts above the cotyledonary node at development stage V1 and above the primary leaf node at stage V2 had reduced height and greater diameter of the plant neck. Contrary to the observations of other researchers, greater branching occurred in the witness, or in the treatment that received cutting of only the cotyledons at VC stage (Barzan et al, 2016). The works found that plants with removal presented lower height, one of the possible justifications is the induction of secondary growth more quickly compared to plants without removal (Tancredi et al, 2004;Tancredi et al, 2006).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…These authors observed in two treatments, that plants submitted to cuts above the cotyledonary node at development stage V1 and above the primary leaf node at stage V2 had reduced height and greater diameter of the plant neck. Contrary to the observations of other researchers, greater branching occurred in the witness, or in the treatment that received cutting of only the cotyledons at VC stage (Barzan et al, 2016). The works found that plants with removal presented lower height, one of the possible justifications is the induction of secondary growth more quickly compared to plants without removal (Tancredi et al, 2004;Tancredi et al, 2006).…”
Section: Resultsmentioning
confidence: 83%
“…It is noted that plant growth after meristem removal is reduced (Barzan, Freiria, Nascimento Junior, & Prete, 2016). These authors observed in two treatments, that plants submitted to cuts above the cotyledonary node at development stage V1 and above the primary leaf node at stage V2 had reduced height and greater diameter of the plant neck.…”
Section: Resultsmentioning
confidence: 96%